2006
DOI: 10.1007/s00127-006-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of mental and physical illness in US Latinos

Abstract: Background-This study describes the prevalence of comorbid physical and mental health problems in a national sample of U.S. Latinos. We examined the co-occurrence of anxiety and depression with prevalent physical chronic illnesses in a representative sample of Latinos with national origins from Mexico, Cuba, Puerto Rico, and other Latin American countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 52 publications
9
64
4
Order By: Relevance
“…This supports a large body of literature regarding the risk of maltreatment in families with histories of parental mental health problems (34). Similar levels of mental and physical health problems are also not surprising in light of the research evidence that supports the high co-occurrence rates of mental and physical illnesses (35,36). Findings have further indicated that the least commonly reported traumatic experience was indirect exposure to rape (emotional abuse group, 5%; sexual abuse group, 7%; non-abuse group, 2%).…”
Section: Indirect Exposure To Traumatic Eventssupporting
confidence: 73%
“…This supports a large body of literature regarding the risk of maltreatment in families with histories of parental mental health problems (34). Similar levels of mental and physical health problems are also not surprising in light of the research evidence that supports the high co-occurrence rates of mental and physical illnesses (35,36). Findings have further indicated that the least commonly reported traumatic experience was indirect exposure to rape (emotional abuse group, 5%; sexual abuse group, 7%; non-abuse group, 2%).…”
Section: Indirect Exposure To Traumatic Eventssupporting
confidence: 73%
“…More recent epidemiological studies have also shown Puerto Ricans to have higher odds for psychiatric disorder than other Latinos (Alegria et al, 2007;Ortega et al, 2006). A distinguishing characteristic of island-born Puerto Ricans is that they enjoy citizenship at birth (unlike foreign-born Latinos), but they may feel more discriminated against when compared with other Latinos and non-Latino Whites, which could increase their risk for et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The National Latino and Asian American Study (NLAAS) has been described in detail elsewhere Heeringa et al, 2004;Ortega et al, 2006). The original study makes use of both national Latino and Asian samples; however, we only report on the Latino sample here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies consistently show an association between asthma and depression (1,(8)(9)(10)(11)(12); however, temporality of the association has not been established (13). Mental health problems can impact awareness of and adherence to the treatment of asthma; thus, depression is associated with poor asthma control, which can lead to an increase in asthma exacerbations (14)(15)(16).…”
Section: At a Glance Commentarymentioning
confidence: 99%